THE EFFECTIVENESS OF CHEST COMPRESSION EXERCISE USING THE “CPR TRAINER” APPLICATION BASED ON ANDROID ON THE SPEED OF DOING CHEST COMPRESSIONS STUDY ON A MANEKIN - Setianingsih Setianingsih; Lestari Eko Darwati; Naimatur Rizkiyah; Ahmad Asyrofi (Indonesian Journal of Community Health Nursing, 2022)
Introduction: The problem of cardiac arrest is currently the number one cause of death in the world so that fast treatment is needed, namely cardiopulmonary resuscitation (CPR). Nursing students are prospective health workers who must have basic skills in performing CPR, but most have not been able to perform chest compressions at the right speed. Achieving these abilities requires an appropriate learning media, one of which is by using the "CPR Trainer" application. This study aims to determine chest compression exercises using the "CPR Trainer" application on the speed of doing chest compressions in 8th semester nursing students at STIKES Kendal. Method: This research used a quasi-experimental with pretest posttest with one grub design. Sampling using purposive sampling technique on 22 8th semester students at STIKES Kendal using mannequins, counters, stopwatches, androids and observation sheets as research tools. Results: Data analysis using the Wilcoxon test showed that there was no relationship between chest compression exercises using the "CPR Trainer" application on the speed of performing chest compressions with a value of = 0.638 (p> 0.005). Conclusion: This can be influenced by the exercise factor because the more a person is exposed to the "CPR Trainer" application, the easier it is for someone to remember the rhythm of the compression speed on the simulator doll.   Keywords: application CPR trainer ; CPR; chest compression speed